Investigating ion-release from nanocomposites in food simulant solutions: Case studies contrasting kaolin, CaCO3 and Cu-phthalocyanine. (December 2020) - Zhang, Zhen; Kappenstein, Oliver; Ebner, Ingo; Ruggiero, Emmanuel; Müller, Philipp; Luch, Andreas; Wohlleben, Wendel; Haase, Andrea
Highlights: A bulk-filled polypropylene with a metal-organic nanopigment and a doubly coated paperboard with a nanoscaled kaolin filler were investigated. Up to 60 % release of Ca (from CaCO3 base coating) vs. 0.4% of Al and max. 0.7% of Si (both from kaolin top coating) were released from paperboard. The release was mainly ionic but the presence of a few nanoparticles (NPs) consistent with Kaolin but not with CaCO3 was confirmed as well. No Cu release was detected from the polypropylene plates and consequently no released pigment nanoparticles were found. High ionic release rates occur for soluble NPs when the food simulant is able to penetrate into the nanocomposite and reach the NPs. Abstract: Nanocomposites, due to their enhanced properties, are interesting for various industrial applications. Investigating a possible release of the incorporated nanoparticles (NPs) is a central part in their safety assessment. Here we analysed two different nanocomposites, polypropylene (PP) containing a nanoscaled Cu-phthalocyanine pigment and a paperboard containing nanoscaled kaolin filler. The release of kaolin and CaCO3 from the paperboard was assessed at room temperature in five different food simulant solutions, i.e. water, 3% (w/v) acetic acid solution (HAc) and aqueous ethanol (EtOH) solutions at 10 %, 50 % and 95 % (v/v). Cu-phthalocyanine release from PP was assessed in 3% (w/v) HAc and 10 % (v/v) EtOH at 40 °C. Quantification was based on measuring Al and Si (kaolin) and Cu (Cu-phthalocyanine) using inductive coupled plasma mass spectrometry (ICP-MS). For the coated paper, release could be detected in different solutions with highest release of Al (3.6 μg/cm 2, corresponding to 0.4 % of kaolin content) and Ca (1, 200 μg/cm², corresponding to 60 ± 18 % of CaCO3 content) in 3% HAc. The presence of NPs, occasionally consistent with Kaolin, but not with CaCO3 was confirmed using single particle ICP-MS and TEM. In contrast, no Cu release was detected from the PP plates and consistently no NPs were found. In conclusion, high ionic release rates occur for soluble NPs when the food simulant solution is able to reach the NPs, i.e. can penetrate into the nanocomposite. This study is an important contribution in understanding possible human health risks of nanocomposites being increasingly used in different applications.